Michelin-starred restaurant diner return willingness: A case study from Thailand - Rattanaparinyanon, Harit; Vuthisopon, Sujira; Saengnoree, Amnuay; Siripongdee, Surapong (Edelweiss Applied Science and Technology, 2024)
This study investigates the factors influencing the return willingness (RW) of diners at Michelin-starred restaurants in Thailand. The focus is on understanding how service novelty (SN), new product innovation (NPI), culinary standards (CS), and diner satisfaction (DS) contribute to diners' intentions to return. A quantitative approach was employed using structural equation modeling (SEM) to analyze data collected from a sample of 320 diners. The study examined the direct and total effects of the variables on RW. The analysis revealed that service novelty, new product innovation, culinary standards, and diner satisfaction collectively account for 75% of the variance in return willingness (R² = 0.75). Service novelty, new product innovation, and culinary standards exhibit significant direct effects on return willingness, with total effect (TE) values of 0.87, 0.79, and 0.76, respectively. Diner satisfaction also significantly impacts return willingness, with a TE value of 0.42. All nine proposed hypotheses were supported, confirming the positive influence of SN, NPI, CS, and DS on diners' return willingness. The study underscores the critical role of continuous innovation, high culinary standards, and exceptional diner satisfaction in fostering repeat business. These factors are integral to enhancing customer loyalty at Michelin-starred restaurants in Thailand. The findings offer valuable insights for restaurant managers aiming to boost customer loyalty and sustain long-term success. Emphasizing service innovation, maintaining high culinary standards, and ensuring diner satisfaction can significantly improve diners' return willingness.